The Land and the A.I.R.: Revisioning Experiential Learning on a Canadian Campus - Flanagan, Kyla; Stowe, Lisa; Martineau, Christine; Kenny, Natasha; Kaipainen, Erin (Experiential Learning and Teaching in Higher Education, 2024)
In Canada, the Truth and Reconciliation Commission highlights our roles as educators to reflect Indigenous cultures and knowledges in post-secondary teaching and learning. Developing an inclusive definition of experiential learning in consultation with Indigenous scholars is essential. This newly revised experiential learning framework represents a living document shaped by ongoing dialogue and input from the campus community, reflecting our commitment to Indigenous reconciliation and holistic education. Grounded in the principles of holistic pedagogy inherent in Indigenous ways of learning, we propose a renewed definition of experiential learning – learning by doing, being, connecting and reflecting. This paper introduces the A.I.R Framework (Authentic experience, Intentional design, Reflection), which is a flexible model for high-quality, inclusive experiential learning that is adaptable to both curricular and co-curricular contexts. We also provide a visual tool for portraying and describing experiential learning in terms of the primary focus or purpose of the experiential learning and the environment in which the experiential learning occurs.